Climate Smart Agriculture Guidelines to improve the viability of Smallholder Farming Enterprises in Southern Africa - Marongwe, Sepo; Magagula, Futhi; Mitti, Joyce; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Climate change can manifest in various ways, including altered precipitation patterns, increased temperatures, and more frequent extreme weather events. These factors can adversely affect crop yields, jeopardizing food security and the livelihoods of the majority of the population dependent on agriculture. Agriculture in Southern Africa Development Community (SADC) is a major contributor to the national economy and is estimated to contribute about 17% of SADC’s gross domestic product (GDP). Smallholder farmers in Southern Africa contribute up to 90% of food production. However, many of the production systems lack the support to ensure the profitability of smallholder farmers, leaving their livelihoods at stake. Most of these smallholders are women who are the primary producers of food. Approximately 70% of southern Africa’s population relies on this sector for livelihood opportunities, encompassing both employment and income. Unfortunately, it is one of the sectors that is underperforming due to declining and highly variable trends in rainfall. This in turn has affected the national agricultural production in the region. For the past 2 decades, SADC member states have reported reduced crop yields as a result of climate variability and trends. For instance, the 2022 Global Report on food crises indicated that about 43 million people in the 11 SADC countries experienced acute food insecurity. This highlights that food systems remain highly sensitive to shifts in climate, including variability, severity and frequency of extreme climatic events. Moreover, the region is considered a hotspot as a result of climate change impact.